EMBODIED ENERGY PADA DINDING BAMBU ANYAMAN DAN PLESTER - Jurizat, Aldissain; Ramadhan, Try (Jurnal Arsitektur ZONASI, 2020)
Abstract: Buildings consume high energy and cause an increase in CO2 gas emissions to the environment. This energy consumption is known as embodied energy where energy is used in the production and maintenance processes of buildings. In buildings, the largest consumption of embodied energy is contained in the walls. Among the various materials and construction of building walls, the trend of the plaster bamboo wall has been significantly increased because it has several advantages for the environment. This research was conducted to measure the embodied energy contained in bamboo wall construction located in Kampung Buyut Cipageran, Cimahi City. This research method uses Inventory Carbon and Energy (ICE) data from the University of Bath and Indonesian National Standard as the basics data for the calculation. The analysis has been conducted by calculating the basics data and the design drawings. The result showed that the embodied energy in the bamboo walls had a value of 230.61 MJ/m2. This result is lower than the known standard for brick wall with 440 MJ/m2. The bamboo wall is proved to be more efficient in energy use than conventional wall with brick as the main construction.Keywords: bamboo wall; embodied energy;Â Abstrak: Bangunan mengkonsumsi energi yang cukup tinggi dan mengakibatkan peningkatan emisi gas CO2 ke lingkungan. Penggunaan energi ini diketahui sebagai embodied energy dimana energi digunakan dalam proses produksi dan perawatan bangunan. Dalam suatu bangunan, penggunaan embodied energy terbesar terletak pada dinding. Dari berbagai material dan konstruksi pembentuk dinding bangunan, dinding bambu plester menjadi tren terbaru karena memiliki beberapa keunggulan dalam keramahan terhadap lingkungan. Penelitian ini dilakukan untuk mengukur embodied energy yang terdapat pada komponen dinding bambu di salah satu bangunan Kampung Buyut Cipageran, Kota Cimahi. Metode pengukuran menggunakan data Inventory Carbon and Energy (ICE) dari University of Bath dan petunjuk analisis pekerjaan konstruksi dari SNI. Hasil analisis menunjukkan bahwa embodied energy pada dinding bambu plester memiliki nilai 230,61 MJ/m2. Jika dibandingkan dengan dinding bata plester konvensional yang memiliki standar 440 MJ/m2, dinding bambu plester lebih efisien dalam penggunaan energi dalam siklus hidupnya.Kata Kunci: dinding bambu; embodied energy;.